Body image during the menopausal transition: a systematic scoping review - Pearce, G.; Thøgersen-Ntoumani, Cecilie; Duda, J. (Routledge, 2014)
This scoping review aimed to examine women’s body image during the menopausal transition systematically. A systematic search strategy and exclusion criteria were applied to ensure that only relevant research was included in the review. A total of 15 studies in 17 papers were included highlighting an equivocal relationship between body image and the menopausal transition. The menopausal transition is complex and individual, and should not be examined as a simple positive or negative transition. There is a sense of confusion for women experiencing the menopausal transition due to contradicting medical advice and societal expectations of body image. Currently, the research consists of exploratory-based studies that highlight the importance of researching this field further to aid adaptive coping and self-management across this transition.